Mono-oxo molybdenum(VI) and tungsten(VI) complexes bearing chelating aryloxides: synthesis, structure and ring opening polymerization of cyclic esters - Sun, Ziyue; Zhao, Yanxia; Prior, Timothy J.; Elsegood, Mark R.J.; Wang, Kuiyuan; Xing, Tian; Redshaw, Carl (Dalton Transactions, 2019)
The mono-oxo aryloxide complexes [M(O)(L1)2] (M = Mo (1·hexane), W(2·2MeCN)) have been prepared from [Mo(O)(Cl)4] or [W(O)(Ot-Bu)4] and two equivalents of the di-phenol 2,2/-ethylidenebis(4,6-di-tert-butylphenol) L1H2, respectively. Use of in-situ generated [Mo(O)(Ot-Bu)4] with two equivalents of L1H2 also led to the isolation of 1·2MeCN. In the presence of adventitious oxygen, attempts to generate in-situ [Mo(O)(Ot-Bu)4] and reaction with one equivalent of L1H2 afforded the bi-metallic complex [Mo(O)(L1)(-O)Li(THF)(MeCN)]2·2MeCN (3·2MeCN). Use of the tetra-phenol α,α,α′,α′-tetrakis(3,5-di-tert-butyl-2-hydroxyphenyl)-p-xyleneH4 (L2H4) with [Mo(O)(Oi-Pr)4] led to the isolation of {[Mo(O)]L2}2 (4), whilst the analogous tungsten complex {[W(O)]L2}2 (5) was isolated from the reaction of L2H4 with [W(O)(Ot-Bu)4]. Similar reaction of p-tert-butylcalix[4]areneH4 (L3H4) with [Mo(O)(Oi-Pr)4] afforded ([Mo(O)L3(NCMe)]·3MeCN (6·3MeCN). Modification of known routes were employed to access the complexes [W(Cl)2L3]·3.5MeCN (7·3.5MeCN) and ([W(O)L3(NCMe)] (8), whilst use of [WO(Ot-Bu)4] with L3H4 unexpectedly afforded [W(Ot-Bu)2L3]·MeCN (9·MeCN). The molecular crystal structures for 1 – 9 are reported, and the ability of these complexes to act as catalysts for the ring opening polymerization (ROP) of epsilon-caprolactone (epsilon-CL), delta-valerolactone (delta-VL) and gamma-pentadecalactone (gamma-PDL) has been investigated. The molybdenum complexes 1 and 4 were the best performers for epsilon-Cl and delta-VL, but all complexes exhibited poor control and were also inactive toward the ROP of PDL.
Keywords: Inorganic Chemistry